ANALISIS FAKTOR PENYEBAB KESULITAN BELAJAR PPKn DI SD - Riska Nur Aisah; Siti Masfuah; Wawan Shokib Rondli (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
This study aims to explain the types of PPKn learning difficulties and the factors that cause learning difficulties experienced by fourth grade students at SDN Klakahkasih. This research uses a qualitative approach with a case study design. The subjects in this study were fourth grade teachers, parents, and fourth grade students who were identified as having PPKn learning difficulties. Data collection techniques used in this study are observation, interviews, documentation and field notes. Data analysis techniques used in this study are data reduction, data presentation, and verification/conclusion. The results showed that 1) learning difficulties experienced by fourth grade students at SDN Klakahkasihan were difficulties in understanding the concept of Civics, difficulties in understanding teacher explanations, difficulties in understanding the meaning of the questions and difficulties in applying positive attitudes towards Pancasila values ​​in everyday life. 2) the factors that cause learning difficulties in Civics consist of internal factors and external factors. Internal factors include illness, low intelligence, student interest in Civics learning is still low, and student motivation in Civics learning tends to be low. While external factors include school environmental factors, namely the use of Civics learning media which is less innovative and variations of teaching teachers tend to use conventional methods, family environmental factors are parents pay less attention to student learning activities, activities in society, namely students have too many activities so that student learning activities become neglected, as well as mass media factors, namely the influence of the use of gadgets and TV.